(untitled) (Journal of Bio-Science, 2019)
Medicinal plant extract contains bioactive molecules and these molecules are benefited to mitigate, eradicate or cure diseases. In advent to search for new medicinally important plant, the current paper deals to select the most effective and promising plants which are suitable for controlling tea leaf’s thrips (Scirtothrips bispinosus) based on extracts concentration and death affect over time. To fulfill the specific objectives, five medicinal plants extracts viz. Ipomoea crassicaulis, Lantana camara, Ipomoea hederaceaa, Glycosmis arborea, and Justicia gendarussa had been used with four different concentrations. From statistical analysis using One-way ANOVA and post hoc test, it was found that Ipomoea crassicaulis and Lantana camara are the most promising of all the experimented plants extracts based on both time and concentration. In the study, average mortality was found 0.47, 1.67, 1.93 and 2.53 for concentration of 1%, 5%, 10% and 15% respectively. Analysis based on different concentrations reveals that average mortality of thrips increases significantly with the increase of concentrations. Coefficient of variance was found minimum for Ipomoea crassicaulis and Lantana camara plants with range of 5.44 to 6.71 based on time and concentration. So, it could be concluded that these two plants are the most effective plants for controlling the tea thrips. For the other plants, ranks were found as Ipomoea hederaceaa, Glycosmis arborea and Justicia gendarussa respectively as well. J. bio-sci. 28: 87-93, 2020